Development of Digital Puzzle Media Based on Project-Based Learning to Improve Narrative Writing Skills of Elementary School Students - Jian Alfian; Sri Dewi Nirmala; Nidya Chandra Muji Utami (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
Writing skills are one of the basic competencies that must be mastered by elementary school students because they serve as the foundation for the development of language skills at subsequent levels. This study aims to analyze the impact of integrating Project-Based Learning (PjBL) and digital picture-series puzzle media on improving narrative writing skills among elementary school students through a Systematic Literature Review (SLR) approach. Narrative writing skills remain low due to conventional teaching practices and the limited use of interactive media that stimulate imagination and sequential thinking. The SLR was conducted by identifying, selecting, evaluating, and synthesizing 18 relevant articles published between 2018 and 2024. The results show that (1) digital puzzle media effectively enhance students’ ability to structure storylines and describe characters; (2) PjBL significantly improves motivation, creativity, and learning autonomy; and (3) the integration of PjBL and puzzle media offers a synergistic effect on narrative writing performance. However, no study has directly and comprehensively combined these two approaches for narrative writing in elementary school contexts, indicating a research gap.